Entre o terreiro e a escola: Lei 10.639/2003 e intolerância religiosa sob o olhar antropológico - Araújo, Patrício Carneiro (2015)
As a result of a doctoral research, this work investigates religious pluralism, diversity, religious intolerance and racism in the context of the Law 10.639/2003. This research demonstrates how racism took different forms in Brazil, assuming in the first instance that religious intolerance against the practitioners of Afro-Brazilian religions is a form of racism. In the case study, this phenomenon is expressed by the desavowal of the African cultural heritage represented by these religions. The investigation is constituted by an incursion into the universe of both schools and terreiros, throught a methodical interlocution with people who transit between terreiros and schools. The research period has been reinforced also by the dynamics of the wider religious context in Brazil, where an increasing intensification of persecutions and violence against the Afro-religious population has been registered. Moreover, a worrisome escalation of conflicts that make clear the terrible relation between racism and religious intolerance has been observed. Therefore, the main content of this work represents a prospect on the current situation concerning religious intolerance and racism in Brazil. Here it is argued that the Federal Law 10.639/2003, which prescribes the introduction of African and Afro-Brazilian History and Culture courses in primary schools in the whole country, is not satisfactory implemented because of the institutional racism that is present in the school environment